Fear less : poetry in perilous times - Smith, Tracy K. (Norton shorts., 2025)
"Drawing on deep passion and personal experience, former US Poet Laureate Tracy K. Smith demystifies the art form that has too often been mischaracterized as "inaccessible," "irrelevant," or "intimidating." She argues that poetry is rooted in fundamentally human qualities innate to our capacities to love, dream, question, and cultivate community. Lifting the veil on her own creative process, Smith shows us how reading and writing poetry allows us to better confront life's many uncertainties and losses, build camaraderie with strangers, and understand ourselves more fully. In six insightful chapters, she grounds readers in the technical elements of the craft and provides close readings of the works of contemporary poets such as Joy Harjo, Danez Smith, and Francisco Márquez, alongside classic poems by Dickinson, Keats, Millay, and others. By reimaging and reexamining the age-old art form, Fear Less is a warm invitation to find meaning, consolation, and hope through poetry for poetry fans and newcomers to the art form."--